Bone turnover markers and bone mineral density in prepubertal obese children: Bone health in prepubertal childhood obesity - Taha, Ola; Elhwary, Amany; Shoeib, Sarah M.; Rashad, Yosra Fouad Mohammed; Ata, Dina (Paediatrica Indonesiana, 2024)
Background Growing evidence suggests that childhood obesity has an impact on bone metabolism. Its entails of bone resorption, destruction of mature mineralized bone by osteoclasts followed by ossification, bone formation by osteoblasts, to maintain the dynamic nature of bone. Serum C-telopeptide of collagen cross-links (CTX) is considered a bone resorption marker while serum procollagen type I N-propeptide (PINP) is considered abone formation marker. Previous studies have reported the abnormality of these bone turnover marker in obese children. Objective To compare bone turnover markers and bone mineral density (BMD) in obese prepubertal children to those of normoweight children. Methods Bone metabolism was evaluated by measuring serum PINP as a bone formation marker and CTX level as a bone resorption marker by enzyme-linked immunosorbent assay. We used dual-energy X-ray absorptiometry (DEXA) scan to evaluate BMD in 60 prepubertal children with obesity and 30 healthy prepubertal normoweight children. Results The CTX was significantly higher in the case group compared to the control group (P=0.001). The case group also had significantly lower mean BMD (P=0.001) and BMD Z-score (P=0.001). C-telopeptide of collagen cross-links in the case group had significant positive correlations with waist circumference (P=0.001), BMI (P=0.001), and BMI Z-score (P=0.001). Significant negative correlations were found between waist circumference, BMI, and BMI Z-score with procollagen type I N-terminal propeptide, BMD, and BMD Z-score. Conclusion Obesity has a negative impact on bone health. Low BMD was associated with high CTX in prepubertal obese children.